1991
DOI: 10.1161/01.atv.11.6.1667
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue proteinases and inhibitors in abdominal aortic aneurysms. Involvement of the vasa vasorum in the pathogenesis of aortic aneurysms.

Abstract: T he development of irreversible dilations of the infrarenal aorta has been attributed to hemodynamic disturbances as well as to structural and metabolic changes within the vessel wall. 1 -2 Chemical and histological analyses have demonstrated significant decreases in the two major structural proteins, collagen and elastin, in dilated vascular tissue from patients undergoing corrective surgery for abdominal aortic aneurysm (AAA) disease. 34 Experimentally, it has been shown that circumferential arterial wall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(81 citation statements)
references
References 44 publications
2
79
0
Order By: Relevance
“…5 Immunolocalization studies have indicated that some MMPs produced in aneurysms were associated with proliferative microvessels. 13 Collectively, these earlier observations together with findings from the present study implicated a potential pathway for aneurysm rupture involving angiogenesis and its elaboration of MMPs. The localized elevation of these proteases in areas of active neovascularization may have a role in focal extracellular matrix degradation and AAA rupture.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…5 Immunolocalization studies have indicated that some MMPs produced in aneurysms were associated with proliferative microvessels. 13 Collectively, these earlier observations together with findings from the present study implicated a potential pathway for aneurysm rupture involving angiogenesis and its elaboration of MMPs. The localized elevation of these proteases in areas of active neovascularization may have a role in focal extracellular matrix degradation and AAA rupture.…”
Section: Discussionsupporting
confidence: 78%
“…11 The medial layer of the infrarenal human abdominal aorta, unlike the thoracic aorta, is not normally supplied by microvessels from the adventitial vasa vasorum. 12 Neovascularization of the medial layer is a consistent feature of established AAAs; 13 however, the role of this pathological angiogenic response in aneurysm rupture has never been investigated. 14,15 As pathological neovascularization occurs in close spatial proximity to the collagen and elastin network of the aortic media, the expression of MMPs during such angiogenic response may lead to proteolytic disruption and degradation of aortic media.…”
mentioning
confidence: 99%
“…4,22 Recently, MMP-12 was reported to be prominently expressed by aneurysm-infiltrating macrophages within the media of human AAA. 5 The roles of MMP-9 and MMP-12 in the pathogenesis of AAA have been investigated in a mouse model of elastase-induced aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…The vessels of the vasa vasorum form the pathways by which inflammatory cells access the aortic intima and media. 10 Medial neovascularization and decreased vascular smooth muscle cells also characterize AAA lesions. The intraluminal thrombus may contribute to the process by causing a functional hypoxia at the luminal intima and inner media, thus inducing subsequent neovascularization and inflammation.…”
mentioning
confidence: 99%